The nature and extent of migrants, immigrants, and refugees' trust in the social institutions of their host countries: a scoping review - Godinho Nascimento, Helena; Abdulkarim, Sultan; Arikati, Geetika; Meyer, Samantha B. (Frontiers in Political Science, 2025)
IntroductionOne of the most significant drivers of the public's decision-making is trust. Trust is a critical factor when making decisions in the face of uncertainty and risk. This same principle applies to trust in our social institutions, which is the topic this paper explores. Institutional trust may be especially important for migrant groups whose vulnerabilities are furthered by the decrease in institutional trust. As such, this review aims to investigate the nature and extent of immigrants, migrants, and refugees' institutional trust (and adjacent concepts) in social institutions.MethodsA scoping review was done using the PRISMA-ScR's guideline and Arksey and O'Malley's framework. A total of 81 articles were selected from four databases following screening, and then data were charted using three extraction tables. Data were organized following 5 main objectives relating to: trust theories and explanations (objective 1), recommendations and solutions targeting different social institutions (objective 2), across population group comparisons (objective 3), defining trust concepts (objective 4), and areas for future research (objective 5).ResultsFindings revealed that many different theories and definitions of institutional trust exist across studies suggesting that institutional trust is a complex and nuanced concept that may vary across different migrant groups, contextual factors, and social institutions of focus. As well, we note the heterogeneity of immigrant groups and how this may relate to the various factors identified as shaping institutional trust. Not a lot of recommendations were presented, and these were mostly community-based. Lastly, research gaps were identified to inform future research and inform efforts and strategies to build institutional trust among migrant groups.DiscussionThese findings, accompanied by other results, demonstrated the significance of trust in migrants when it comes to their successful integration, as well as their health and well-being over time. We emphasize the need for trust interventions at different societal levels, and the need to target both immigrant populations and social institutions. We conclude that establishing trust in one institution will help build trust in other institutions, such as the public health and healthcare system institutions.